Obtenção de biodiesel a partir de óleos e gorduras residuais - Trentini, Caroline Portilho (2019)
The transesterification from the grease trap waste (GTW) using pressurized ethanol in a catalyst free medium, aiming the continuous production of fatty acid ethyl esters (FAEE) was studied. The lipid fraction of the grease trap waste was separated and characterized, as well as it was used to conduct the reactions by evaluating the operational variables in order to maximize the formation of GTW, the two-step reaction, the addition of different water contents in ethanol, and the thermal decomposition of fatty acids. The RCG lipids showed a high content of free fatty acids, and the main fatty acids identified were oleic and linoleic. The results obtained demonstrate that the higher availability of ethanol and the increase in pressure and temperature resulted in higher yields. For the reaction performed in one step the maximum yield of FAEE was ~93% and the two step reaction increased the yield to ~96% at 300 °C, 20 MPa, oil/ethanol ratio of 1:2 and 40 minutes. When using the addition of water in ethanol in the reaction medium up to 2.5 wt% of water led to the increase of the esters in low residence time, and with the increase of the reaction time the yield was not affected compared to the reaction without addition of water, effect similar to that observed with 5 wt% water. With the use of 7.5 and 10 wt% water, the yield of esters was reduced. At the temperature > 300 °C and longer residence times the thermal degradation of the fatty acid esters, mainly of ethyl linoleate and with that the reduction of the yield of FAEE, occurred. The highest ester yield in the reactions with addition of water was 92.6%, at 300 °C, 30 min of reaction and 2.5 wt% of water in ethanol, in which condition the presence of ~5.5% of unreacted compounds (monoglycerides, diglycerides and triglycerides). The obtained results showed that the addition of water in ethanol shows similar yield to the reaction conducted without addition of water, which can reduce ethanol-related production costs. The lipid fraction of RCG can be transformed into biodiesel using ethanol from the two-step reaction.